Malaysia’s Agricultural Production Dropped and the Impact of Climate Change: Applying and Extending the Theory of Cobb Douglas Production - Ahmad Fawad Entezari; Kelly Kai Seng Wong; Fazlin Ali (AGRARIS: Journal of Agribusiness and Rural Development Research, 2021)
Under climate change, Malaysia's agricultural production showed decreasing in recent decades. This study tries to fill in the gaps to applying and extending the Cobb Douglas production function theory to examine the impact of climate change and economic factors on Malaysia's agricultural production. Using Engle-Granger (EG) test with 37 years of data from 1980 to 2016. The findings showed that the long-run estimated coefficients for rainfall, temperature, and interest rate were -0.338, -0.024, and -0.029, respectively. This indicates that each additional percent in rainfall, temperature, and interest rate will be affected the agricultural production, on average, to decrease by 0.338%, 0.024%, and 0.029%, respectively, holding others constant. Besides that, the long-run elasticity of real GDP per capita, employment, and Trend showed 0.509, 0.513, and 0.119, respectively. Increase 1% of real GDP per capita will lead to the agricultural production to increase about 0.509%, ceteris paribus. The elasticity of employment showed that each 10% increase in agricultural employment will increase the agricultural production on average 5.13%, ceteris paribus. Furthermore, the trend estimated coefficient showed that the agricultural production will have a constant growth rate which is 0.119% per year. All variables were statistically significant to explain the long-run agricultural production. The short-run rainfall, temperature, employment, and Trend were statistically significant to determine the short-run production growth. Therefore, advanced technology and the latest information on climate change are relevant to boost agricultural production growth. In addition, policymakers also suggested establishing lower interest rate loan facilities and no labor shortage in this industry.